Preparedness of Maize Farmers against Climate Change Risks in Saki-West Local Government Area, Oyo State, Nigeria - K. O. Ogunjinmi; Y. Joshua; K. G. Adeosun; M. Umunna; O. O. Adenuga; A. O. Ogunlusi; E. O. Fakoya; A. A. Ogunjinmi; R. A. Ibrahim (Journal of Applied Sciences and Environmental Management, 2024)
Farmers must be prepared to face climate change risks to ensure sustainable maize production. This paper aimed to investigate maize farmers' preparedness against climate change risks in Saki-West Local Government Area, Oyo State, Nigeria using appropriate standard methods with 113 respondents through a questionnaire survey. The study found that respondents observed increasing rainfall (x̄=1.50) and temperature (x̄=133).  Respondents primarily prepared for climate change by purchasing drought-resistant varieties and agrochemical inputs (x̄=3.27). The study found that farmers had difficulty in preparing for climate change due to a lack of access to extension agents (x̄=3.58), credit (x̄=3.47), and government policy (x̄=3.43). The multiple linear regression model found that participation in farmers' associations (β = -2.407, t=0.001) and access to extension agents (β = -4.645, t=0.002) were substantially associated with farmers' readiness for climate change risks. Therefore, improved extension services are recommended to the farmers.